2015
DOI: 10.7554/elife.09214
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive transcription read-through promotes aberrant expression of oncogenes and RNA chimeras in renal carcinoma

Abstract: Aberrant expression of cancer genes and non-canonical RNA species is a hallmark of cancer. However, the mechanisms driving such atypical gene expression programs are incompletely understood. Here, our transcriptional profiling of a cohort of 50 primary clear cell renal cell carcinoma (ccRCC) samples from The Cancer Genome Atlas (TCGA) reveals that transcription read-through beyond the termination site is a source of transcriptome diversity in cancer cells. Amongst the genes most frequently mutated in ccRCC, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
112
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 24 publications
3
112
1
Order By: Relevance
“…This allows many RNAs to be generated from intergenic regions (Vilborg et al, 2015) and, in fact, the global efficiency of termination is known to change in cancer (Grosso et al, 2015; Kannan et al, 2011; Maher et al, 2009), viral infection (Nemeroff et al, 1998; Rutkowski et al, 2015), and osmotic stress (Vilborg et al, 2015). Once produced, some readthrough transcripts have been proposed to help maintain the nuclear scaffold during osmotic stress (Vilborg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This allows many RNAs to be generated from intergenic regions (Vilborg et al, 2015) and, in fact, the global efficiency of termination is known to change in cancer (Grosso et al, 2015; Kannan et al, 2011; Maher et al, 2009), viral infection (Nemeroff et al, 1998; Rutkowski et al, 2015), and osmotic stress (Vilborg et al, 2015). Once produced, some readthrough transcripts have been proposed to help maintain the nuclear scaffold during osmotic stress (Vilborg et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Upon osmotic, oxidative or heat stress, transcriptional patterns of thousands of genes show prolonged Pol II progression, extending several kilobases further downstream of the PAS than observed in non-stress conditions 119 . Reduced poly(A)-processing has been coupled to read-through transcription 120122 , and RNA-seq studies indicate that read-through transcription, indeed, produces long RNA molecules that mostly remain in the nucleus 119 (FIG. 5).…”
Section: Co-transcriptional Processingmentioning
confidence: 99%
“…Recent studies reveal that stress can reduce the efficiency of transcription termination (8)(9)(10). Transcription termination involves elongation through the cleavage and polyadenylation (polyA) signal and subsequent cleavage of the nascent RNA, followed by the addition of nontemplated A residues to the 3′ end to produce an mRNA.…”
mentioning
confidence: 99%
“…Typically, the extended RNA is quickly degraded by exonucleases that access the unprotected 5′ end generated by cleavage at the polyA site (12,13). However, recent studies show that various stress and disease states, including osmotic stress (10), HSV-1 infection (9), and renal carcinoma (8), increase both the levels and length of transcripts mapping to regions downstream of the cleavage and polyadenylation sites. Our previous study (10) showed that these transcripts are continuous with the RNAs generated from the upstream protein-coding gene, suggesting that they result from alterations in cleavage and polyadenylation and/or termination events.…”
mentioning
confidence: 99%